Assessment of the hemodynamic characteristics of Absorb BVS in a porcine coronary artery model. (15th January 2017) - Tenekecioglu, Erhan; Torii, Ryo; Bourantas, Christos; Abdelghani, Mohammad; Cavalcante, Rafael; Sotomi, Yohei; Crake, Tom; Su, Solomon; Santoso, Teguh; Onuma, Yoshinobu; Serruys, Patrick W.
ABSTRACT: Background and aim: Local hemodynamic changes are one of the main factors that determine the vessel wall biological response after stent/scaffold implantation. Computational fluid dynamic studies provide an opportunity to investigate the rheological effects of implanted stent/scaffold. The aim of this study was to assess the local hemodynamic microenvironment in scaffolded segments in porcine coronary models. Methods: In six epicardial coronary arteries of healthy mini-pigs, six Absorb bioresorbable vascular scaffolds (Absorb BVS) were implanted. Optical coherence tomography(OCT) was performed after scaffold implantation and the images were fused with the angiographic data to reconstruct the three-dimensional coronary artery anatomy. Blood flow simulations were performed, and endothelial shear stress(ESS) distribution was estimated for each scaffolded segment. In a linear mixed-effect model, the contributing factors for low (< 1.0 Pa) ESS levels were assessed. At 30-day post-implantation, histopathological assessment was performed at 2 scaffolds. Results: In scaffolded segments, the median ESS was 0.57 (IQR: 0.29–0.99) Pa. In linear mixed-effect analysis, cross-section area was associated with low shear stress levels. In scaffolded segments, the percentage of the recirculation zone per scaffolded luminal surface was 3.26 ± 2.07%. At 30-day histopathological assessment of implanted vessel segments revealed minimal injury score, minimal neointimal inflammation and minimal adventitial inflammation scores with moderate endothelial coverage. Fibrin accumulation was seen at 95.69 ± 2.47% of the struts. Conclusion: The thick rectangular strut design of the Absorb BVS incited flow disruptions with low shear stress inducing fibrin accumulation. CFD assessment can be used to guide improvements in the scaffold design for a more "hemo-compatible" geometry.